2018
DOI: 10.3390/app9010014
|View full text |Cite
|
Sign up to set email alerts
|

Reliability Modeling and Evaluation Method of CNC Grinding Machine Tool

Abstract: Featured Application: The proposed research aims to provide one accurate and reliable evaluation method for the subsystem and system of electromechanical equipment.Abstract: How to determine subsystem's reliability and evaluate the whole machine's reliability of the CNC (computer numerical control) grinding machine tool is important for reliability design and promotion. Each subsystem was modeled by a different distribution based on collected data and the models were optimized by the modified gray correlation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…It is necessary to emphasize that to ensure an improvement in the reliability of the system, a separate study is necessary, which must be carried out considering a modeling and evaluation of the proposal with strategies such as the Monte Carlo method [29], in addition to taking into account the reliability of the same electrical network where the HDT would operate [30].…”
Section: Topologymentioning
confidence: 99%
“…It is necessary to emphasize that to ensure an improvement in the reliability of the system, a separate study is necessary, which must be carried out considering a modeling and evaluation of the proposal with strategies such as the Monte Carlo method [29], in addition to taking into account the reliability of the same electrical network where the HDT would operate [30].…”
Section: Topologymentioning
confidence: 99%
“…According to the failure data of NC machine tool, the fault distribution function of each component of CNC machine tool can be obtained after parameter estimation of reliability model and fitting hypothesis test [10,11]. Correlation distribution functions are listed in Table 1.…”
Section: Subsystem Reliability Modelmentioning
confidence: 99%
“…The results showed that the experimental cost of ensuring reliability was reduced, with an error of less than 10% between the experiment and the simulation. Liu et al (19) utilized the operating data of a grinding machine to build a model of each of its subsystems. They optimized the models through corrected gray correlation.…”
Section: Introductionmentioning
confidence: 99%